Legal Perspectives on the Online Trade of Imported Secondhand Clothing (Thrifting) Under Indonesian Positive Law - Dada, Syafrudin Eko Haryanto Kembang; Rustam, Muhammad Rizal (Cognitionis Civitatis et Politicae, 2024)
The rapid advancement of technology has revolutionized various business sectors, including the global clothing trade. Alongside new apparel, the importation of secondhand clothing into Indonesia, commonly referred to as "thrifting," has gained popularity due to its affordability. However, this practice has raised concerns regarding its legality and impact on the national economy. This paper examines the legality of buying and selling imported secondhand clothing (thrifting) online from the perspective of Indonesian positive law. Using a normative juridical method, the research reveals that both online and offline thrifting practices violate several regulations, including the Job Creation Law, the Consumer Protection Law, and the Minister of Trade’s Regulation on Export and Import Prohibited Goods. Key factors driving the persistence of thrifting in Indonesia include the country’s openness to imports and the demand for affordable, high-quality clothing. Despite its growing popularity, thrifting poses significant risks, such as health hazards and detrimental effects on the domestic garment industry.